(3cJGH GdeaUds - (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s
(3ChdgG (B:s
(3bGd GdTjN GdReNTQi Gddg CMeO Ydi Cf LYdfi ef YdeGA GdYQHjI GdbSe GdChd ai GdCSeGA GdbSe GdKGfi ai GdCaYGd GdbSe GdKGdK ai GdMQha s
(3BNQgG (B:s
(3hEPG cGfhG eef jMPahf eY EecGf GdEOZGe ai jJSY hjJbi age eY YOe EecGfg CMPa hGddg CYde s
(3GdfSNI HgG MhGTs
(3fSNJ Yf fSNI bhHdJ HfSNI HNW GdUZGfi GdJi bGHdgG HfSNI GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
Keywords: (3GdbQGAGJ hGdJLhjOs